Contributions to the Technological Adoption Model for the Peruvian Agro-Export Sector - Huerta, Hugo Vega (2021)
This paper proposes a technology adoption model called TAM 4, based on the TAM model considering the trust and perceived risk factors to the adoption of technology in response to governments’ concern to achieve competitiveness in the most important economic activities. The methodology used considers the predictive method. The sample was selected from 67 companies related to foreign trade that carry out agro export tasks, with a confidence level of 90% and an error percentage of ± 10% and the 0.787 of Cronbach’s Alpha obtained for the instrument’s validation. In conclusion, 97% of the companies informally adopt technology. This shows that 68% of the companies surveyed in the sector would be willing to adopt the model.